Utility of circulating serum miRNAs as biomarkers of early cartilage degeneration in animal models of post-traumatic osteoarthritis and inflammatory arthritis. Issue 3 (March 2017) - Kung, L.H.W.; Zaki, S.; Ravi, V.; Rowley, L.; Smith, M.M.; Bell, K.M.; Bateman, J.F.; Little, C.B.
Summary: Objective: The purpose of this study was to determine if serum microRNA (miRNA) signatures were biomarkers of early cartilage degeneration in preclinical mouse models of post-traumatic osteoarthritis (OA) and inflammatory arthritis. Methods: Cartilage degeneration was induced in 10–12 week old male C57BL6 mice by destabilization of the medial meniscus (DMM) or intra-articular injection of methylated-bovine-serum-albumin (AIA), with sham-operated or saline-injected control animals ( n = 6/treatment/time). Total serum RNA and knee joints were isolated at 1, 4 and 16 weeks post-induction. Cartilage degeneration was scored histologically. Serum miRNA expression profiling was performed using Agilent microarrays and validated by qPCR. Results: DMM-operated and AIA mice had characteristic cartilage degeneration (proteoglycan loss, chondrocyte hypertrophy, structural damage), that increased significantly with time compared with controls, and with distinct temporal differences between arthritis models. However, expression profiling revealed no statistically significant dysregulation of serum miRNAs between AIA vs saline-injected or DMM vs sham-operated control mice at the critical early disease stages. The inability to detect DMM or AIA serum miRNA signatures compared with controls was not due to the insensitivity of the expression profiling approach since significant changes were observed in miRNA expression between the arthritis models and between time points. Conclusion: While distinct patterns of progressive cartilage degradation were induced in the arthritis models, we were unable to identify any serum miRNAs that were significantly dysregulated in early stages of disease compared with controls. This suggests circulating serum miRNAs may not be useful as cartilage biomarkers in distinguishing the early or progressive stages of arthritis cartilage degeneration.